Profile of lichen planus in Bangladesh - Khondker, L; Wahab, MA; Khan, SI (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):250-53. The abstract of this article is available on the PubMed website